Efektivitas Pemberian Lumbar Stabilization Exercise terhadap Peningkatan Kemampuan Fungsional pada Kasus Low Back Pain Myogenic: Literature Review - Hikhmah, Sabilla Nur; Noviana, Mita; Pahlawi, Riza (UI Scholars Hub, 2022)
Low back pain is the most common symptom experienced by people of all ages. However, low back pain myogenic can cause pain, spasms, muscle weakness, limited range of motion (ROM), and muscle imbalances, resulting in decreased core and lower back muscles, and limited mobility of the lumbar spine, causing a decrease in ability functional. In Indonesia, the prevalence of people affected by myogenic LBP has increased, almost 75% of them are related to work. From the search results with various databases, 75 articles were found which were then filtered and 21 articles were selected. But of the 21 articles, there will be more. The final result after selection is 5 articles. Knowing the effectiveness of providing lumbar stabilization exercise to improve functional ability in myogenic low back pain case by knowing the dose and method given. There is an increase in functional ability in patients with low back pain myogenic by offering lumbar stabilization exercise at a dose given for 6 weeks, 3 sessions/week, 8 repetitions with duration of 30-60 minutes/session. Providing lumbar stabilization exercise can be an intervention solution to improve functional ability of you pas attention to several things